2020
DOI: 10.1021/acs.jpcb.9b09578
|View full text |Cite
|
Sign up to set email alerts
|

Distance Dependence of Electronic Coupling in Rigid, Cofacially Compressed, π-Stacked Organic Mixed-Valence Systems

Abstract: A series of new π-stacked compounds, 1,8-bis­(2′,5′-dimethoxybenzene-1′-yl)­naphthalene (1), 1,4-bis­(8′-(2″,5″-dimethoxybenzene-1″-yl)­naphthalen-1′-yl)­benzene (2), and 1,8-bis­(4′-(8″-(2‴,5‴-dimethoxybenzene-1‴-yl)­naphthalen-1″-yl)­benzene-1′-yl)­naphthalene (3), have been synthesized and characterized herein as precursor molecules of monocationic mixed-valence systems (MVSs). The three-dimensional geometries of these compounds were determined by X-ray crystallography. A near-orthogonal alignment of the na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 105 publications
0
8
1
2
Order By: Relevance
“…Molecular MV-CT systems feature two oxidizable or reducible building blocks covalently linked through molecular bridges.T he molecular bridges serve two roles:a sa n electronic coupling medium and as ad istance keeper.T hey are typically built from carbon frameworks,s uch as aromatics, [8][9][10][11] alkynes, [8,12] cyclophanes, [13][14][15] oligo-p-phenylene vinylenes, [16,17] etc., or combinations thereof. [18,19] All of these allow the electronic coupling to be fine-tuned at either short or long distances.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular MV-CT systems feature two oxidizable or reducible building blocks covalently linked through molecular bridges.T he molecular bridges serve two roles:a sa n electronic coupling medium and as ad istance keeper.T hey are typically built from carbon frameworks,s uch as aromatics, [8][9][10][11] alkynes, [8,12] cyclophanes, [13][14][15] oligo-p-phenylene vinylenes, [16,17] etc., or combinations thereof. [18,19] All of these allow the electronic coupling to be fine-tuned at either short or long distances.…”
Section: Introductionmentioning
confidence: 99%
“…Sie fungieren als elektronisches Koppelmedium und als Distanzhalter. Typischerweise sind sie aus Kohlenstoffgerüsten, wie Aromaten, [8–11] Alkinen, [8, 12] Cyclophanen, [13–15] Oligo‐ p ‐phenylvinylenen [16, 17] usw., oder Kombinationen davon aufgebaut [18, 19] . Diese molekularen Brücken ermöglichen eine Feinabstimmung der elektronischen Kopplung sowohl bei kurzen als auch bei langen Distanzen.…”
Section: Introductionunclassified
“…Molekulare MV-CT-Systeme weisen zwei oxidierbare oder reduzierbare Bausteine auf,w elche kovalent durch molekulare Brücken verbunden sind. Die molekularen Brücken erfüllen zwei Zwecke.S ie fungieren als elektronisches Koppelmedium und als Distanzhalter.T ypischerweise sind sie aus Kohlenstoffgerüsten, wie Aromaten, [8][9][10][11] Alkinen, [8,12] Cyclophanen, [13][14][15] Oligo-p-phenylvinylenen [16,17] usw., oder Kombinationen davon aufgebaut. [18,19] Diese molekularen Brücken ermçglichen eine Feinabstimmung der elektronischen Kopplung sowohl bei kurzen als auch bei langen Distanzen.…”
unclassified
“…A number of representative structural motifs used for through‐space electronic interactions have been reported: cyclophanes, 13–17 1,2‐phenylene derivatives, 18–21 bicycloalkanes, 16,22,23 various kinds of sp 3 hydrocarbons, 24–29 1,8‐naphthalene, 30–33 and metal–organic frameworks 34,35 . The magnitudes of H 12 range from tens to thousands of wavenumbers depending on the bridge systems.…”
Section: Introductionmentioning
confidence: 99%
“…In this manuscript, we report a new mixed‐valence system (MVS), [1,8‐bis(2′,5′‐dimethoxy‐4′‐methyl‐[1,1′‐biphenyl]‐4‐yl)naphthalene] • + ( 1 • + , Chart 1), in which two dimethoxytoluene redox centers, hereinafter designated as D (or D 1 and D 2 if necessary), are separated by 1,8‐diphenylnaphthalene spacer featuring a van der Waals D‐A interplanar separation (3.50–3.70 Å). In our previous works, we have shown that the charge transfer through the orthogonally attached naphthalene pillars is prohibited and the donor–acceptor electronic coupling is mediated by direct through‐space π – π interaction in 2 • + 30 . We put one more phenylene unit between redox active dimethoxytoluene and naphthalene moieties so that the overall through‐bond distance between two D units is far more separated, and thus through‐bond charge transfer between neutral and cationic D units is essentially precluded.…”
Section: Introductionmentioning
confidence: 99%